PTH-077 Fertility and pregnancy related misconceptions in female patients with inflammatory bowel disease. (22nd June 2015) - Zammit, S Chetcuti; Caruana, M; Katsanos, K; Mantzaris, G; Cesarini, M; Kopylov, U; Zammit, L; Brookes, M; Ellul, P
Abstract : Introduction: Reproductive issues in patients with inflammatory bowel disease (IBD) have been shown to be inadequately addressed by clinicians. Patients appear to opt for voluntary childlessness due to misconceptions about fertility and pregnancy. Method: Female IBD patients were prospectively recruited from 5 different European centres. They were interviewed through the use of a questionnaire. Results: 233 patients were recruited (mean age 40; SD±11.9). The mean age at diagnosis was 31.4 years (SD±11.2). 85.5% patients with ulcerative colitis (UC) had a Montreal classification of E2 or E3. Crohn's disease (CD) patients predominantly (64.7%) had a non-stricturing and non-penetrating phenotype. Only 57.9% of patients were counselled on IBD and fertility (gastroenterologists 46.8%; gynaecologists 7.30%). 27.5% had admitted to considering voluntary childlessness. This correlated with lack of counselling delivered by health care professionals (coefficient 1.147; p < 0.003). Reasons included: (i) fear of harm from the disease to the baby (52.8%); (ii) fear of harm from medications to the baby (61.4%); (iii) fear of passing on IBD to the baby (57.9%); (iv) fear of having a complicated pregnancy (51.5%); (v) being incapable of taking care of their child after birth (8.6%). 19.7% expressed fear of infertility following the diagnosis of IBD. 8.2% were aware that the mode of delivery could be influenced by IBD. 15.5% and 36.5% knew that surgery could influence fertility and mode of delivery respectively. Regarding IBD medications during pregnancy: (i) 15.0% thought that all medications should be stopped; (ii) 12.0% believed that some medications should be stopped; (iii) 63.1% were unsure about what to do with medications. 1.7% of patients stopped medications without consultation with clinical teams. 26.6% of patients were uncertain if patients with IBD could breast feed. 37.0% said that they could not. 47.0% thought that females with IBD could not breastfeed due to medications crossing into the breast milk. 15.9% were counselled to undergo regular pap smears. 61.8% received information about the HPV vaccine. Conclusion: The effects of inadequate fertility counselling in patients with IBD in Europe might contribute to the high levels of voluntary childlessness. A number of misconceptions about pregnancy and delivery exist. This study highlights the need to improve care for this cohort of patients through the development of a multidisciplinary team management. Further studies might allow us to evaluate the most effective way of delivering improved support for these patients. Disclosure of interest: None Declared.